The sustainability status of cut rose farming in Batu City: uncovering data and facts from Indonesia's largest cut rose producing city - Tiasmalomo, Riska; Salam, Muslim; Iswoyo, Hari; Jamil, Muhammad Hatta; Tenriawaru, A. Nixia; Dermawan, Rahmansyah; Kamarulzaman, Nitty Hirawaty; Akhsan; Heliawaty; Fudjaja, Letty; Rahmadanih; Ridwan, Muhammad; et al. (Elsevier B.V., 2025)
Batu City, East Java, produces the most cut roses in Indonesia. The city's cut rose cultivation has long been the primary source of income for local farmers. However, cut rose producers face many issues that imperil their farms. Therefore, this study aimed to analyze the sustainability status of cut rose flower farming and sensitive indicators that affect its sustainability. This research was conducted in October 2024. Structured interviews with 155 rose-cut farmer respondents provided this study's primary data. The data analysis method used was multidimensional scaling (MDS). The results of the study show that the sustainability of cut rose farming in Batu City is categorized as “quite sustainable” with an average score of 62.57. This empirical fact suggests that the farm has a sufficiently long period to continue cultivation. Then, the sensitive indicators significantly affecting ecological sustainability were the land elevation, chemical fertilizer use, and crop waste management. Regarding economic sustainability, the most sensitive indicators were the farm profit, market scale, and market chain. Next, the most sensitive indicators affecting social sustainability were the intensity of extension, farming experience, and family participation in farming. Finally, the sensitive indicators that most influence the sustainability of technological innovation are transportation technology, the adoption of environmentally friendly cultivation innovations, and marketing technology. The results suggest that cut rose farming could be more sustainably run if specific key indicators were addressed; these include steep land slopes, a lack of marketing and promotion, frequent disputes among farmers, and inadequate cultivation technology.